Implementasi Algoritma Linear Congruent Method Pada Pengacakan Soal Kuis dalam Aplikasi Mobile Learning Anemia Berbasis Android (MobiliA) - Herlambang, Bambang Agus; Wibowo, Setyoningsih; Choirunnisa, Choirunnisa; Setyawati, Vilda Ana Veria (Jurnal Transformatika, 2021)
Anemia is a lack of blood condition with reduction in hemoglobin as one of indicator.  According to data from the Basic Health Research in 2013, the prevalence of anemia sufferers in Indonesia was high at 37.1%. The figure was almost close to severe public health problems with an anemia prevalence limit of more than 40%. However, this was not accompanied by low public knowledge about anemia.Therefore, researcher created an anemia mobile learning application based on android to increase people knowledge about anemia in everytime.There were quizzes randomly issued using the Linear Congruent Method algorithm. Linear Congruent Method algorithm, which was an algorithm that produced random permutations from a finite set. Testing Linear Congruent Method (LCM) algorithm was able to produce an effective randomization problem, where there was no repetition of the same value if the value of the declared variable meets the determination parameters of the existing LCM Algorithm i.e. the increment value and modulus must be relatively prime.